Novel Sutureless Scleral Fixated IOL for Inadequate or Absent Capsular Support - Georgios Sidiropoulos; Elisabeth Siskou; Spyridon Koronis; Paris Tranos; Zisis Gatzioufas; Miltos Balidis (Journal of Ophthalmology, 2022)
Purpose. To evaluate the clinical outcome and safety profile of a new sutureless scleral fixation (SSF) technique using a single-piece foldable acrylic Carlevale intraocular lens. Methods. In this case study, 27 eyes of 27 patients were implanted with an SSF single-piece IOL because of inadequate or absent capsular support. The hand-shake technique used during surgery was combined with the creation of scleral pockets in order to secure the IOL haptics. The BCVA was evaluated in the 1st and 6th month in every patient and in the 12th and 24th months, when possible. Also, we evaluated the improvement achieved in spherical equivalent values from baseline to the 6th month after the procedure. Intraoperative and postoperative complications were assessed. Results. The mean age was 69.1 ± 14.9 years, and the mean follow-up was 13.6 ± 4.8 months. Indications of scleral-fixated IOL included dislocated posterior chamber IOL (40.7%), dislocated anterior chamber IOL (11.1%), subluxated traumatic cataract (18.5%), subluxated nontraumatic cataract (18.5%), and aphakia (11.1%). Concurrent PPV was performed on eight of the eyes (32%). The mean preoperative logMAR BCVA increased from 0.85 ± 0.59 baseline to 0.44 ± 0.30 one month after surgery p<0.01 and 0.36 ± 0.34 p<0.003 six months after surgery. The baseline refractive status expressed in SE was 4.3 ± 6.4 D, and the postoperative status was −0.5 ± 0.99 D. Postoperative complications included vitreous hemorrhage (7.4%), hypotony (7.4%), transient IOP elevation (3.7%), and postoperative cystoid macular oedema (3.7%). The IOL was very well centered and stable in every case during the follow-up period. Conclusion. The use of the SSF technique with implantation of a single-piece foldable acrylic Carlevale IOL seems to be a safe and effective alternative method that provides good preliminary results in cases where capsular support is inadequate or absent. Long-term stability results would be required to evaluate the benefit of this novel surgical approach in order to compare it with other existing methods.